2009
DOI: 10.1051/0004-6361/200911963
|View full text |Cite
|
Sign up to set email alerts
|

The mass profile of early-type galaxies in overdense environments: the case of the double source-plane gravitational lens SL2SJ02176-0513

Abstract: Context. The Strong Lensing Legacy Survey (SL2S) provides a sample of the strong lensing events associated with massive distant galaxies, some of which lie in the outskirts of galaxy groups and clusters. Aims. We investigate the internal structure of early-type galaxies in overdense environments, where tidal forces are expected to alter dark matter haloes of infalling galaxies. Methods. SL2SJ02176-0513 is a remarkable lens for the presence of two multiply-imaged systems at different redshifts lensed by a foreg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…Note also that Tu et al (2009) found that another system of images is associated with this lens. These images correspond to a more distant source, and the light from this second source is influenced by the potential of the first source.…”
Section: Previous Workmentioning
confidence: 74%
See 4 more Smart Citations
“…Note also that Tu et al (2009) found that another system of images is associated with this lens. These images correspond to a more distant source, and the light from this second source is influenced by the potential of the first source.…”
Section: Previous Workmentioning
confidence: 74%
“…Another possibility is to assume that the two images are not merged and that the yellow contour in Fig. 1 corresponds to the image of the second bright spot, as considered by Tu et al (2009). Still since the separation between the images is large the slope of the local model would have to be small.…”
Section: General Properties Of the Solutionmentioning
confidence: 99%
See 3 more Smart Citations